Impact of anti-sticking coating technology on shear strength at the clay-metal interface in cohesive strata - Liu, Pengfei; Sun, Shicheng; Yang, Zhao; Ji, Fuquan; Xu, Chao; Zhu, Hanbiao (Frontiers in Earth Science, 2023)
Tunnel and underground engineering constructions within cohesive strata often encounter numerous challenges associated with adverse geological conditions, such as shield clogging. Shield clogging is closely linked to the shear strength exhibited at the clay-metal interface. To investigate the impact of anti-sticking coating technology on the shear strength at the clay-metal interface, a series of direct shear tests were conducted. The obtained test results revealed an initial increase in shear stress at the clay-metal interface as shear displacement increased, eventually reaching a state of stabilization. The shear strength exhibited a gradual increase initially, followed by a significant increase, and eventually reached a plateau with the rise in the consistency index. It was observed that the adhesion between the anti-adhesion coating and clay was relatively weak, but the presence of the anti-adhesion coating effectively reduced the risk of shield clogging.